Proceedings of the Winter Simulation Conference 2014 2014
DOI: 10.1109/wsc.2014.7020005
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the September 8, 2011, San Diego blackout

Abstract: The development of predictive tools for emergency management has recently become a subject of major consideration among emergency responders, especially at the federal level. Often the news of an impending high-consequence threat causes significant stress on these agencies because of their inability to apprise management of probable impacts with sufficient certainty. This paper documents Argonne National Laboratory's effort to demonstrate the predictive capability of its newly enhanced tool called EPfast in es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…As of 2010, several power systems blackouts have occurred, which left millions of customers stranded for hours. For instance, a power outage occurred in the Pacific Southwest on 8 September 2011, which lasted for about 12 h affecting 2.7 million residents of San Diego, California, Arizona and Mexico [35][36][37]. In this event, tripping of a major transmission line during peak load led to the system collapse.…”
Section: Blackouts Around the Globementioning
confidence: 99%
See 1 more Smart Citation
“…As of 2010, several power systems blackouts have occurred, which left millions of customers stranded for hours. For instance, a power outage occurred in the Pacific Southwest on 8 September 2011, which lasted for about 12 h affecting 2.7 million residents of San Diego, California, Arizona and Mexico [35][36][37]. In this event, tripping of a major transmission line during peak load led to the system collapse.…”
Section: Blackouts Around the Globementioning
confidence: 99%
“…In this event, tripping of a major transmission line during peak load led to the system collapse. During that time, San Diego experienced a total blackout and simulations in [35] showed that insufficient load shedding led to the cascading effects. Earlier in the same year on 4 February 2011, power system blackout occurred in Brazil due to flaws in the transmission lines and it lasted for about 16 h [38].…”
Section: Blackouts Around the Globementioning
confidence: 99%
“…For instance, on August 14, 2003, US and Canada experienced a wide-area blackout that affected around 50 million people and caused a loss of about 10 billion U.S. dollars [6]. On September 8, 2011, the cascading blackout occurred in the Pacific Southwest, resulting in approximately 2.7 million people with no access to power [7].…”
Section: 1)mentioning
confidence: 99%